Analysis of spatial variation of internal migration In Iraq for the year 2013 - عبد حمد, عذراء (Al-Adab Journal, 2018)
Is one of population growth components of immigration and is essential for the re-distribution of the population and differing regional growth in the formation of various Trakiphm, which has social consequences and significant demographic, has included search and social survey results and economic families in Iraq (IHSES for the year 2013) survey covered pan Iraq's provinces (18) province and the number of households surveyed (25 488) Dynasty form each district (216 households) spread between the present and the countryside, has been searching on my way adopted (place of birth and place of residence) and through the results represented Kurdistan region more provinces attractive for residents and came Maysan province over the provinces of Iraq expelling the inhabitants and the form factor of security and stability in the forefront of the factors affecting the internal migration